Adult-onset hyperinsulinaemic hypoglycaemia in clinical practice: diagnosis, aetiology and management. Issue 7 (October 2017) - Challis, Benjamin G; Powlson, Andrew S; Casey, Ruth T; Pearson, Carla; Lam, Brian Y; Ma, Marcella; Pitfield, Deborah; Yeo, Giles S H; Godfrey, Edmund; Cheow, Heok K; Chatterjee, V Krishna; Carroll, Nicholas R; et al.
Abstract : Objective: In adults with hyperinsulinaemic hypoglycaemia (HH), in particular those with insulinoma, the optimal diagnostic and management strategies remain uncertain. Here, we sought to characterise the biochemical and radiological assessment, and clinical management of adults with HH at a tertiary centre over a thirteen-year period. Design: Clinical, biochemical, radiological and histological data were reviewed from all confirmed cases of adult-onset hyperinsulinaemic hypoglycaemia at our centre between 2003 and 2016. In a subset of patients with stage I insulinoma, whole-exome sequencing of tumour DNA was performed. Results: Twenty-nine patients were identified (27 insulinoma, including 6 subjects with metastatic disease; 1 pro-insulin/GLP-1 co-secreting tumour; 1 activating glucokinase mutation). In all cases, hypoglycaemia (glucose ≤2.2 mmol/L) was achieved within 48 h of a supervised fast. At fast termination, subjects with stage IV insulinoma had significantly higher insulin, C-peptide and pro-insulin compared to those with insulinoma staged I–IIIB. Preoperative localisation of insulinoma was most successfully achieved with EUS. In two patients with inoperable, metastatic insulinoma, peptide receptor radionuclide therapy (PRRT) with 177 Lu-DOTATATE rapidly restored euglycaemia and lowered fasting insulin. Finally, in a subset of stage I insulinoma, whole-exome sequencing of tumour DNA identified the pathogenic Ying Yang-1 ( YY1 ) somatic mutation (c.C1115G/p.T372R) in one tumour, with all tumours exhibiting a low somatic mutation burden. Conclusion: Our study highlights, in particular, the utility of the 48-h fast in the diagnosis of insulinoma, EUS for tumour localisation and the value of PRRT therapy in the treatment of metastatic disease.